Dealing with thrombocytopenia during anticoagulation with heparins for active venous thromboembolism: a play-it-safe practical approach - Abdel-Razeq H; Ismael Y (Dove Medical Press, 2011)
Hikmat Abdel-Razeq, Yousef IsmaelSection of Hematology and Medical Oncology, Department of Internal Medicine, King Hussein Cancer Center, Amman, JordanPurpose: Thrombocytopenia is not uncommonly encountered following active anticoagulation of thromboembolism with unfractionated or even low-molecular-weight heparins. In this report, and utilizing a case study, we will address issues related to the diagnosis and treatment of heparin-induced thrombocytopenia (HIT) in a community-based clinical practice.Methods: The case of a 73-year-old female patient who was recently diagnosed with gastroesophageal junction cancer and who developed left lower extremity deep vein thrombosis (DVT) while on active chemotherapy is presented. Following the initiation of anticoagulation, a significant drop in platelet counts was noted and a clinical diagnosis of HIT was made. Articles published in English addressing issues related to anticoagulation and thrombocytopenia were accessed from PubMed and are discussed.Results: HIT is not uncommon, but its diagnosis can occasionally be difficult to confirm. Alternative anticoagulants might not be available for immediate use and many require special expertise for appropriate use. Fondaparinux, a synthetic pentasaccharide, is approved for active anticoagulation of DVT and pulmonary embolism and can be given once daily subcutaneously at a fixed dose with no need for monitoring. Many recent reports described the successful use of this agent in the treatment of HIT.Conclusion: HIT can be difficult to diagnose; diagnostic tests are generally not available in most hospitals and the available ones lack the sensitivity and specificity needed to confirm such diagnosis. Additionally, the alternative anticoagulants are not widely available. In such circumstances, fondaparinux can be used as an alternative anticoagulant.Keywords: anticoagulation, thrombosis, thrombocytopenia, heparin-induced thrombocytopenia